2021
DOI: 10.1111/ssqu.12936
|View full text |Cite
|
Sign up to set email alerts
|

Population Aging and Its Impact on the Country's Economy

Abstract: Objective. The present article raised the pressing issue of population aging in Russia and investigated the challenges this phenomenon poses to the social security system. As modern studies show, this challenge is typical for both developing and developed countries. The paper intended to propose ways of reforming the pension system of the Russian Federation to ensure its independence from the state budget. Methods. The provided suggestions were based on the analysis of the current demographic problems in Russi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…They appear to be more urgent in China, given the following circumstances. China failed to reach a sufficient level of national wealth per inhabitant, and coverage of the country’s pension system is uneven (Li et al, 2018 ; Lukyanets et al, 2021 ; Wang, 2019 ). Therefore, the socialisation of older people is crucial for preserving the workforce and maintaining a healthy psychological climate in a country with a rapidly ageing population (He et al, 2019 ; Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They appear to be more urgent in China, given the following circumstances. China failed to reach a sufficient level of national wealth per inhabitant, and coverage of the country’s pension system is uneven (Li et al, 2018 ; Lukyanets et al, 2021 ; Wang, 2019 ). Therefore, the socialisation of older people is crucial for preserving the workforce and maintaining a healthy psychological climate in a country with a rapidly ageing population (He et al, 2019 ; Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social participation and engagement in paid work are the most crucial factors in maintaining social resilience. In many developing countries, ageing populations can heavily influence decision-making and choice processes (Lukyanets et al, 2021 ; Webster and Pierce, 2019 ). Ageing contributes to the formation of multi-age groups where relationships are age-driven.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the above studies and theories, many scholars use linear models to study the impact of the aging population on economic growth, but this research method has major flaws. For example, Yang et al [3] found that the aging population would inhibit economic growth by reducing the ecological footprint; Lukyanets et al [4] also found that the aging population would reduce economic growth in Russia; Scott et al [5] and Liu [6] got the same conclusion. However, Pham and Vo [7], Mamun et al [8], and Wang et al [9] found that the aging population would promote economic growth.…”
Section: Introductionmentioning
confidence: 94%
“…Cristea, Noja, Dănăcică, & Ştefea, [12] have linked the ageing population to reduced labor productivity and increased poverty risk. Similarly, Lukyanets, Okhrimenko, & Egorova [13] noted that an ageing population reduced the labor force and increased the dependency level, with an impact on economic stability. The literature further concluded that ignorance towards the ageing population has implications on state budget stability and threatens a country's economic prosperity.…”
Section: Introductionmentioning
confidence: 96%